Finishing of orthodontic treatment - Eka Erwansyah; Donald R. Nahusona; Asfiani Arif (Makassar Dental Journal, 2020)
Introduction: The prime reason for a patient to seek orthodontic treatment is to gain an improvement in appearance. An excellent orthodontic finishing is essential and involves a series of procedures such as a good diagnosis, appropriate treatment planning and its implementation. Objective: This article is aimed to describe the achievement of treatment that should be achieved both in terms of the occlusion, aesthetic, until the planning of post-treatment in order to obtainperfect and long lasting results. Methods: Clinical cases in literature are used to illustrate the details of the desired finishing orthodontic treatment. Summary:Steps that performed to obtain good finishing of orthodontic treatment are define the goals of treatment, have a checklist about achievment of treatment, improve the functional occlusion, and reshape the teeth anatomicaly, and planning the retention of orthodontic post-treatment.